The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1063/1.1425445
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of Yb-doped silica glass

Abstract: We have carried out a systematic study of optical emission in Yb-doped fiber glass materials which can be used for fiber laser applications. The stimulated emission crosssections of these materials have been calculated. The wavelength dependence of emission of these materials has been studied. The peak emission cross section in Yb-doped silica glass is 2.6 pm2 and the peak wavelength is at 974 nm. The codopants do not significantly alter the emission cross section or the peak wavelength of this cross section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…, which is the appropriate expression [28]. The parameters [a, b] from the fit are within an order of magnitude of the expected values [37,38]. Note that these Q factor measurements were performed at 980nm or the pump wavelength of the microlaser, and not the lasing wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…, which is the appropriate expression [28]. The parameters [a, b] from the fit are within an order of magnitude of the expected values [37,38]. Note that these Q factor measurements were performed at 980nm or the pump wavelength of the microlaser, and not the lasing wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…31 P experiments were carried out on Bruker Avance-300 spectrometer, operating at the spinning rate of 10 kHz. Typical acquisition parameters are pulse length 3 μs (90°) and recycle delay 90 s. 27 Al experiments were carried out on Bruker Avance-500 spectrometer, operating at the spinning rate of 14 kHz, using pulse length 1.0 μs (30°solid pulse length) and relaxation time of 1 s. 29 Si experiments were carried out on Bruker Avance-500 spectrometer, operating at the spinning rate of 8 kHz, using pulse length 6.0 μs (90°) and relaxation time of 250 s. Reported chemical shift of 31 P, 27 Al and 29 Si were referenced to 85% H 3 PO 4 , an aqueous solution of Al(NO 3 ) 3 (1 M) and liquid tetramethylsilane (TMS), respectively. All tests in this work were performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it can be confirmed that Yb 3 þ is principally located around P 5 þ ions, but not around the Si 4 þ ions in the series of AY glasses. However, no structural relationship between Al 3 þ and Yb 3 þ ions can be obtained through the change of 27 Al NMR spectra because of the second-order quadrupole effect. Fortunately, another detail of 27 Al MAS NMR spectrum with a peak maximum near 35 ppm is well known in aluminophosphate materials and assigned to Al(OP) 4 units [38][39][40].…”
Section: Effect Of P 5 þ On the Spectroscopic Properties Of Yb 2 þ Anmentioning
confidence: 98%
See 1 more Smart Citation
“…These properties contribute to the applications of FP glasses as RE-doped fiber laser matrix. Many researches have showed that Yb 3+ doped FP glasses have a promising future as laser matrix [3][4][5].…”
Section: Introductionmentioning
confidence: 99%